2023
DOI: 10.1111/cid.13195
|View full text |Cite
|
Sign up to set email alerts
|

Focal adhesion formation of primary human gingival fibroblast on hydrothermally and in‐sol‐made TiO2‐coated titanium

Abstract: Optimal cell adhesion of the gingival fibroblasts to dental implants is important for maintaining good implant integration. The aim of this study was to discover, if the nanoporous TiO 2 -coating on titanium alloy substrates is able to increase the cell adhesion of the human gingival fibroblasts (HGF). The study consisted of three differently produced titanium groups: hydrothermally produced TiO 2 -coating (HT), novel TiO 2 -coating made in sol (SOL), and noncoated control group. Primary HGF cells were initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Also, the focal adhesions were significantly longer than in the cells on Ti0.6Zr0.6Nb1.4Ta1.4Mo1.4, suggesting that Ti1.4Zr1.4Nb0.6Ta0.6Mo0.6 was the most potent in stimulating the focal adhesions maturation in the osteoblast cells. It is well known that the maturation of focal adhesions is closely associated with tissue integration of the implanted biomaterials [79], and this finding proves that the nonequiatomic Ti1.4Zr1.4Nb0.6Ta0.6Mo0.6 BioHEA possessed a superior in vitro biological performance when compared to that of SUS-316L alloy. This study brings to attention that by manipulating the alloy compositions in the Ti-Nb-Ta-Zr-Mo bioHEAs, implant biocompatibility can be optimized.…”
Section: In Vitro Biological Performance Of Heasupporting
confidence: 57%
See 1 more Smart Citation
“…Also, the focal adhesions were significantly longer than in the cells on Ti0.6Zr0.6Nb1.4Ta1.4Mo1.4, suggesting that Ti1.4Zr1.4Nb0.6Ta0.6Mo0.6 was the most potent in stimulating the focal adhesions maturation in the osteoblast cells. It is well known that the maturation of focal adhesions is closely associated with tissue integration of the implanted biomaterials [79], and this finding proves that the nonequiatomic Ti1.4Zr1.4Nb0.6Ta0.6Mo0.6 BioHEA possessed a superior in vitro biological performance when compared to that of SUS-316L alloy. This study brings to attention that by manipulating the alloy compositions in the Ti-Nb-Ta-Zr-Mo bioHEAs, implant biocompatibility can be optimized.…”
Section: In Vitro Biological Performance Of Heasupporting
confidence: 57%
“…It is well known that the maturation of focal adhesions is closely associated with tissue integration of the implanted biomaterials [79], and this finding proves that the non-equiatomic Ti 1.4 Zr 1.4 Nb 0.6 Ta 0.6 Mo 0.6 BioHEA possessed a superior in vitro biological performance when compared to that of SUS-316L alloy. This study brings to attention that by manipulating the alloy compositions in the Ti-Nb-Ta-Zr-Mo bioHEAs, implant biocompatibility can be optimized.…”
Section: In Vitro Biological Performance Of Heasupporting
confidence: 55%
“…Different surface modifications of the implant transmucosal component have been studied previously to ensure proper soft tissue attachment and stability. TiO 2 coating is one example of surface modifications that have shown promising potential to improve soft tissue attachment on implant surfaces [ 21 ]. Various techniques have been used to obtain bioactive TiO 2 coatings on implant surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…These interactions can enhance molecular and cellular activities and promote tissue healing at the Ti–tissue interface [ 27 , 28 ]. Several in vitro studies have demonstrated that nanoporous TiO 2 coatings enhanced gingival cell response [ 5 , 21 , 29 , 30 ]. It has been shown that nanostructured TiO 2 coatings with smooth surface topography and good wettability promote favorable fibroblast and epithelial cell responses compared to machined surfaces which ultimately affects the rate and quality of new tissue formation [ 31 ].…”
Section: Introductionmentioning
confidence: 99%